Perancangan Program Peminjaman Dan Pengembalian Buku Pada Perpustakaan (Studi Kasus Smp Pgri 1 Cibinong) - Sarita, Nur; Aria, Ririn Restu; Susliansyah, Susliansyah (STIKOM Tunas Bangsa Pematangsiantar, 2017)
The library is one of absolute means that must be owned by a school because students can get more science and knowledge without having to buy a book of its own. Now an interest read the students also had the higher it should be supported by the school.Library of PGRI 1 Junior High School in Cibinong need once the existence of an application program library that support and provide satisfactory service for the students in the process of borrowing and the return on the book. For that is the writer trying to make final assignment regarding the design of the program and the repayment of loan book at the library of the PGRI 1 Junior High School in Cibinong which is still done manually, starting from the processing of the data members of the data processing, book loaning, transaction processing, transaction processing, and returns to the making of reports, thus allowing the process to take place at the time the error occurred in the logging, less akuratnya the report is made and the delay in the search for the required data. The design of the program is the best solution to solve the problems that exist in the library, as well as with the design of the program can be reached by an activity which is effective and efficient in supporting activities at the library. Then this in the design of the program better than the manual systems to run more effectively and efficiently as well as lending system and return books that are now more conducive than with the previous system.